The Problem of Relativism and Its Implication on Contemporary Issues in Islam Based on Al-Attas’ Worldview Theory - Mohammad Muslih; Ahmad Faizin Soleh; Martin Putra Perdana; Ach Fuad Fahmi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
The relativism problem –allegedly has become a frightening specter for a stable religious and social existence. Relativism which believes there is no absolute truth; the truth is relative, raises a problem by denying the existence of God's truth and declaring that human is the measure of all things. Even though human statements, when viewed from this review, also become very relatively charged. Therefore, an in-depth study of relativism and its implication for Islam must be investigated. This paper tried to provide a solution problem of relativism by using the worldview theory from Al-Attas, which can guide humans to know the direction and purpose of their behavior in viewing actual reality. The authors used a qualitative research method, collected data on the issues raised from various reading sources such as books and journals, and analyzed data using Al-Attas' theory. Critical analysis methods supported by solid historical reviews found that this understanding of relativism triggered other notions that deconstructed the truth claims of Islam as a complete religion and messed up fixed Sharia law 'śawābit'. Relativism is the root cause of multi-dimensional problems, especially religion and social issues. Therefore, the existence of an ideal moral measure that is universal is necessary and manifest.